A hemochromatosis-causing mutation C282Y is a risk factor for proliferative diabetic retinopathy in Caucasians with type 2 diabetes - Peterlin, Borut; Globočnik Petrovič, Mojca; Makuc, Jana; Hawlina, Marko; Petrovič, Daniel (Journal of human genetics, 2003)
Iron metabolism might be involved in the pathogenesis of type 2 diabetes and in the pathogenesis of diabetic retinopathy. C282Y and H63D mutations in the hemochromatosis (HFE) gene are associated with increased serum iron levels and consequently with hereditary hemochromatosis. In the present study, we searched for a relationship between C282Y and H63D gene mutations and the development of proliferative diabetic retinopathy in Caucasians with type 2 diabetes. For this purpose, 90 subjects with type 2 diabetes with proliferative diabetic retinopathy (PDR) were compared to 133 diabetic subjects without PDR. There was a significantly higher frequency of the C282Y heterozygotes in patients with PDR compared to subjects without it (OR=3.0, 95% CI=1.2–8.0; p =0.02), whereas no association was demonstrated between PDR and H63D genotypes (OR=1.1, 95% CI=0.6–2.2; p =0.7). Logistic regression analysis revealed that the C282Y mutation was a significant independent risk factor for the development of PDR (OR=6.1, 95% CI=1.2–30.5; p =0.027). These data suggest that heterozygosity for C282Y might be a novel risk factor for PDR in Caucasians with type 2 diabetes.